El presupuesto participativo entre democracia, pobreza y desarrollo (2010)
ResumenEste artículo presenta los aspectos centrales de la evaluación del Presupuesto Participativo realizada entre los años 2005-2006 en Medellín (Colombia), para la vigencia fiscal del 2005. Mediante la consulta a diversos estamentos de la sociedad política, civil y administrativa de la ciudad, se logró hacer un balance de la gobernabilidad democrática y la participación, la planeación y el desarrollo local, y la gestión pública, sintetizados en tres niveles: el operativo-funcional, el metodológico-normativo y el estratégicopolítico. La discusión final trata asuntos críticos del Presupuesto Participativo en cuanto a las transformaciones en el poder local, el tejido social y la superación de la pobreza, y retoma los acercamientos a otras experiencias de América Latina y los informes de la administración municipal y la veeduría de Medellín.AbstractThis article presents the results of the evaluative investigation done between 2005-2006 in Medellín (Colombia) about the 2005 participatory budget with the Corregimentales and Communal Consultative Councils (C.C.C.C). This was done through the consultation of diverse estates of the political, civil, and administrative society of the city, in accordance with the phases of management and the fulfillment of the program’s goals and objectives during this year, which facilitated making a balance about democratic governability and participation; planning and local development; and public management synthesized in three levels: the operative-functional, the methodological-normative and the political-strategic. The final discussion will deal with critical issues regarding participatory budgeting in terms of the transformations in the local power, the social woven and the erradication of poverty, retaking the approaches to other experiences of Latin America, and reports of the municipal administration and the veeduría of Medellín.